THE EFFECT OF YOGYAKARTA DESTINATION IMAGE ON BEHAVIORAL INTENTIONS ON DOMESTIC TOURIST - Adrianus Alen Junaidi; Fitri Novia Widjaja; Erna Andajani (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2017)
Tourism is an important economic sector in Indonesia and has developed rapidly into the tourism industry in each province, especially the Special Region of Yogyakarta province which is thick with culture and history. This study aims to determine the influence of destination image of Yogyakarta on behavioral intentions of domestic tourists. The data used in this study are primary data obtained from questionnaires. The sampling technique of this study is non probability sampling. The results of the study showed that the destination image of Yogyakarta has a direct influence on the behavioral intentions of domestic tourists. Destination image assessment can be measured through the variable infrastructure, attraction, value of money, and enjoyment. Because the four variables have high average values, it can be interpreted that destination image of Yogyakarta as a tourist destination has a good influence on domestic tourists.